(untitled) (Medical Forum Monthly, 2024)
Objective: To analyze the 5years data of autopsies with reference to weaponry pattern may offer some help in controlling law and order situation in the country. Study Design: Retrospective Study Place and Duration of Study: The study was conducted at THQ hospital Taxila. 5 years data of autopsies conducted during the years from 2009-2013 was taken and analyzed. Materials and Methods: Autopsy registers from 2009 to 2013 were taken from THQ Hospital Taxila and analysis of the available data was done regarding weaponry pattern, age, sex, area of body targeted and nature of injuries. Results: During 5years 2009-13 total 279 autopsies were conducted. 234 (83.87%) dead bodies were belonged to male and 45 (16.13%) to females. Most of the dead bodies were adult age group, 138 (49.46%) dead bodies were between age 20-40 years, out of which 112 (81.16%) of males and 26 (18.84%)of females. Firearm remained the most common weapon used claiming 177 (63.44%) lives. In 22 (7.88%) deaths blunt weapons were used and only 7 (2.5%) deaths were caused by sharp edged weapon. Head remained the most targeted area as in 88(31.54%) cases. In 76 (27.24%) persons chest was the target. 33 (11.83%) persons was hit on abdomen, while 28(10.04%) dead bodies were found with injuries on neck. In 40 cases (14.34%) no cause of death was detected. Conclusion: The analysis may be used to control law and order situation in the society.